Anaplastic large cell lymphoma presenting as sternal swelling - Narayanan, Santhosh; Prakash, Divya; Subramaniam, Gomathy; Mahadevan, Lakshminarayanan (International Journal of Advances in Medicine, 2018)
Lymphomas involving the sternum are very rare. We report a case of lymphoma presenting as lytic sternal lesion. A 14-year-old girl presented with history of painless swelling of central chest (sternum) of 3 months duration. Fine needle aspiration cytology from the site revealed anaplastic large cell lymphoma. It was confirmed by histopathology and immunohistochemistry. She underwent treatment with chemotherapy but succumbed to her illness after six months of treatment.